STUDIES ON PRODUCTION OF VITAMIN E AND SELENIUM ENRICHED JAPANESE QUAIL MEAT - P. Chitra; S. C. Edwin; M. Moorthy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was conducted to assess the alpha- tocopherol form of vitamin E and selenium level in Japanese quail meat. This trial was conducted in 525 Japanese quail birds fed from day- old to five weeks of age. Experimental birds were randomly divided into seven treatment groups viz.T1- Control ; Basal diet (standard Japanese quail ration), T2 - Basal diet with Vitamin E 150mg/kg; T3 - Basal diet with Vitamin E 300 mg/kg; T4- Basal diet with selenium 0.3mg/kg ; T5- Basal diet with selenium 0.6mg/kg; T6 - Basal diet with combination of Vitamin E 150mg/kg and selenium 0.3mg/kg; T7- Basal diet with combination of Vitamin E 300mg/kg and selenium 0.6mg/kg. Dietary supplementation with the combination of Vitamin E 300mg/kg and selenium 0.6mg/kg indicated significantly enriched alpha- tocopherol and selenium level in liver, thigh and breast muscles of Japanese quail meat.